If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(u + -2) = -4u + -44 Reorder the terms: 9(-2 + u) = -4u + -44 (-2 * 9 + u * 9) = -4u + -44 (-18 + 9u) = -4u + -44 Reorder the terms: -18 + 9u = -44 + -4u Solving -18 + 9u = -44 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. -18 + 9u + 4u = -44 + -4u + 4u Combine like terms: 9u + 4u = 13u -18 + 13u = -44 + -4u + 4u Combine like terms: -4u + 4u = 0 -18 + 13u = -44 + 0 -18 + 13u = -44 Add '18' to each side of the equation. -18 + 18 + 13u = -44 + 18 Combine like terms: -18 + 18 = 0 0 + 13u = -44 + 18 13u = -44 + 18 Combine like terms: -44 + 18 = -26 13u = -26 Divide each side by '13'. u = -2 Simplifying u = -2
| 9+27r=8-12r | | 4u+30=6(u+4) | | .85x+0.05(14-x)=.10(-41) | | 99-115=-4(-4y)-9(2y)+y | | 5(v-4)=5v+20 | | -16+15= | | 2q+379=833 | | -2/9=n/9 | | x(7x+25)=2x^2-9x+48 | | -40x^2=-5x^3-30x | | 6v-27=-3(v-6) | | 10+(-9)= | | -2(3n+6)=3(-n+12) | | (8-x/12)(4-x/12)=64/5 | | 10-6t=5t-10 | | 2y+x=38 | | (3x+4)(x+8)= | | -5(x+2)=-(-5x+1)-x | | -4x^4+8x^3+60x^2=0 | | 0.16=56 | | -15t^3-12t-6=0 | | 35=y+2 | | 1+7n=8n+9 | | 6x+10=4x-32 | | 134x^2+308x+188=8x^2+4x+4 | | -48=-4r | | 0.2=0.004 | | 9x+63=-1 | | -2x-5.8=12.2 | | s=rx+tx | | 0.004=0.2 | | y+.666=4.75 |